Chylous ascites after nephrectomy without lymphadenectomy for malignant rhabdoid tumor of the kidney: A rare occurrence and literature review - Einama Takahiro; Okada Tadao; Sasaki Fumiaki; Todo Satoru (Wolters Kluwer Medknow Publications, 2009)
Chylous ascites (CA) is an extremely rare complication of abdominal surgery in children. This report describes a 4-month-old girl with malignant rhabdoid tumor of the kidney (MRTK), who developed CA after left nephrectomy without lymphadenectomy, and who was successfully treated conservatively with enteral therapy. The literature on CA after nephrectomy without lymphadenectomy for MRTK is reviewed herein, and the clinical problems of postoperative CA are discussed.